Pengaruh Mata Kuliah Kewirausahaan dan Praktik Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Administrasi Bisnis FISIP Universitas 17 Agustus 1945 Surabaya - Sari, Evi Novita; Mulyati, Awin; Maduwinarti, Ayun (Research Journal of Social Science and Economics, 2025)
This study ains to determine the effect of entrepreneurship courses and entrepreneurial practices on student entrepreneurial interest partially, simultaneously, and also dominant. The method in this research uses quantitative methods using multiple linier regression. The sample in this study were active student of Business Administration FISIP Universitas 17 Agustus 1945 Surabaya in the 2019-2020 batch year who had taken entrepreneurship courses and entrepreneurship practices. The population taken was 124 student. The number of samples in this study were 94 students who were calculated using Simple Random Sampling technique. Using questionnaire distribution as a data collection technique. The results obtained are 1) partially shows a significant influence between the variabels of entreprenurship courses (X1) on entrepreneurialinterest (Y) student of Business Administration FISIP Universitas 17 Agustus 1945 Surabaya. 2) there is also a significant influence between the practice of entrepreneurship (X2) on entrepreneurial interest (Y) student of Business Administration FISIP Universitas 17 Agustus 1945 Surabaya. 3) simultaneously shows that Entreprenurship subject and Entrepreneurship Practices have a significant effect on Entrepreneurship Interest of Business Administration FISIP Universitas 17 Agustus 1945 Surabaya.